THE CONCEPT OF FAMILY IN UZBEK AND ENGLISH PROVERBS - Sharopova Muazzamxon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article studies “family” concept and investigates the concept of family in Uzbek and English proverbs and sayings.